Reactualization of Pancasila in Preventing Radicalism and Terrorism - Mujib, Muhammad Abdul (Universitas Negeri Semarang, 2018)
Practicing the values of Pancasila for the nation's young generation must be improved. In the present era, it can be felt if the values of the Pancasila are gradually eroded due to the influence of the current era. Pancasila values are not reflected in a part of Indonesian society as seen from several problems that have emerged lately such as radicalism and terrorism. The emergence of radicalism and terrorism threatens the ideology and soul of the Unitary State of the Republic of Indonesia. There needs to be a personal drive from the outside and inside the nation to overcome the problem. Pancasila reactualization for the younger generation is one of the keys in counteracting radicalism and terrorism. The acts of radicalism and terrorism have an impact on division, loss of diversity and fear for all Indonesian citizens. This research is normative research, the object of study is Pancasila, and the method used in this study is literature study.Practicing the values of Pancasila for the nation's young generation must be improved. In the present era, it can be felt if the values of the Pancasila are gradually eroded due to the influence of the current era. Pancasila values are not reflected in a part of Indonesian society as seen from several problems that have emerged lately such as radicalism and terrorism. The emergence of radicalism and terrorism threatens the ideology and soul of the Unitary State of the Republic of Indonesia. There needs to be a personal drive from the outside and inside the nation to overcome the problem. Pancasila reactualization for the younger generation is one of the keys in counteracting radicalism and terrorism. The acts of radicalism and terrorism have an impact on division, loss of diversity and fear for all Indonesian citizens. This research is normative research, the object of study is Pancasila, and the method used in this study is literature study.